Records - Australian Intervarsity Choral Societies' Association (1968)
The records, which include correspondence and minutes, mainly concern the promotion and management of national choral festivals for Australian university choral societies. They contain the complete records for the 28th (1977) Intervarsity Choral Festival (I.V.C.F.) held in Canberra. Also includes a records inventory and copy of Bullfrog sheet 4.
Manuscript reference: NLA MS 6266.
Guide to collections of manuscripts relating to Australia
Although the Association was formalised in the 1970s, intervarsity festivals, especially between Sydney and Melbourne, began in the 1950s.
Descriptive list available.
Keywords: Australian Intervarsity Choral Societies' Association -- Archives; Choral societies -- Australia